2018
DOI: 10.12659/msm.912336
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Oleuropein Against Cerebral Ischemia/Reperfusion by Inhibiting Neuronal Apoptosis

Abstract: BackgroundIn this study, we investigated the potential neuroprotective effect of oleuropein (OLE) on apoptotic changes via modulating Akt/glycogen synthase kinase 3 beta (Akt/GSK-3β) signaling in a rat model of cerebral ischemia/reperfusion injury (IRI).Material/MethodsSprague-Dawley male rats (12 weeks, n=200) were randomly assigned to 5 groups: sham group, vehicle (IRI+ vehicle) group, OLE (IRI+OLE) group, OLE+LY294002 (IRI+OLE+LY294002) group, and LY294002(IRI+LY294002) group. The rats were subjected to cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In addition to anti‐inflammatory and bone‐protective effects, oleuropein also has potent anti‐apoptotic effects reported through decreased bax and caspase‐3 levels and increased bcl‐2 levels by Zhang et al . Supporting the anti‐apoptotic effect of oleuropein, Potocnjak et al also reported reduced dose‐dependent caspase‐3 and bax expressions with 5, 10, and 20 mg/kg administration of oleuropein ,.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to anti‐inflammatory and bone‐protective effects, oleuropein also has potent anti‐apoptotic effects reported through decreased bax and caspase‐3 levels and increased bcl‐2 levels by Zhang et al . Supporting the anti‐apoptotic effect of oleuropein, Potocnjak et al also reported reduced dose‐dependent caspase‐3 and bax expressions with 5, 10, and 20 mg/kg administration of oleuropein ,.…”
Section: Discussionmentioning
confidence: 90%
“…37 In contrast, the results of the present study showed that oleu- CD68 can be considered as an indicator of accumulated macrophage and monocyte lineage cells, and increased levels in the periodontitis indicate increased inflammation. 45,46 In addition to anti-inflammatory and bone-protective effects, oleuropein also has potent anti-apoptotic effects reported through decreased bax and caspase-3 levels and increased bcl-2 levels by Zhang et al 47 Supporting the anti-apoptotic effect of oleuropein, Potocnjak et al also reported reduced dose-dependent caspase-3 and bax expressions with 5, 10, and 20 mg/kg administration of oleuropein. 48 , 100, and 300 mg/kg doses of oleuropein also exhibited an anti-apoptotic effect in indomethacin-induced toxicity in rats.…”
Section: Inos Bmp-4 Cd68 Caspase-3 and Bcl-2 Immunostaining Resmentioning
confidence: 96%
“…In addition, it preserved the blood-brain barrier structure and attenuated oxidative stress as well as ICH-induced MAPK activation in brain tissue [238]. Also, Ole improved neurological and cognitive outcomes, alleviated brain edema, increased neurotrophic factors, and reduced apoptosis of neural cells after ischemia/reperfusion injury in rat model of cerebral ischemia [239].…”
Section: Oleuropeinmentioning
confidence: 99%
“…Nevertheless, at moment it's unclear whether OLE affects AQP2-S-glutathionylation. Numerous studies revealed that OLE or oleuropein, which is the main constituent of OLE, may have protective roles by inhibiting cell death 38,39 . However, dose-dependent effects have been described in rats receiving OLE.…”
Section: Discussionmentioning
confidence: 99%